Tribal leadership leveraging natural groups to build a thriving organization - Logan, David; King, John Paul 1941-; Fischer-Wright, Halee (Tantor Audio, 2019)
Within each corporation are anywhere from a few to hundreds of separate tribes. In Tribal Leadership, Dave Logan, John King, and Halee Fischer-Wright demonstrate how these tribes develop--and show you how to assess them and lead them to maximize productivity and growth.
Online resource; title from title details screen (OverDrive, viewed April 5, 2019)
Keywords: Leadership; Organizational behavior; Teams in the workplace; Comportement organisationnel; Équipes de travail; Downloadable audio books; Audiobooks; Livres audio